A fivefold linker length reduction in an interpenetrated metal–organic framework via sequential solvent-assisted linker exchange - Cao, Li-Hui; Liu, Xin; Tang, Xiao-Han; Liu, Junyi; Xu, Xiao-Qian; Zang, Shuang-Quan; Ma, Yang-Min (Chemical communications (Cambridge, England), 2019)
A sequential solvent-assisted linker exchange (SSALE) method was used to contract the unit cell dimensions of an interpenetrated layer-pillared Zn-MOF. The 15.3 Å N , N ′-di-4-pyridylnaphthalenetetracarboxydiimide (DPNDI) pillar was replaced stepwise by 9.4 Å trans -1,2-bis(4-pyridyl)ethene (BPE) and 2.8 Å pyrazine (PYZ). Notably, the sequential transformations lead to more than five times reduction in the linker size, which is the largest change in linker size by the SALE method so far.